Pelatihan Manajemen Sumber Daya Manusia Di Rumah Sakit Dalam Rangka Peningkatan Kinerja - Chon Cho Reynols Manday; Supriadi Siagian; Willy Julitawaty; Syawaluddin Syawaluddin; Mila Asmawiani Okta (Jurnal Pemberdayaan Masyarakat, 2024)
A hospital is a healthcare institution that provides comprehensive health care services, including inpatient, outpatient, and emergency care, provided by doctors, nurses, and other healthcare professionals. This community service activity aims to provide comprehensive human resource management training for hospital managers and staff to build a professional and effective work team. The training method includes theory sessions, case studies, role-playing simulations, and group discussions focused on leadership, effective communication, team motivation, and conflict resolution in the workplace. The goal is to enhance participants' managerial skills, strengthen communication skills among team members, build responsive leadership, and develop constructive conflict resolution strategies. The expected outcomes of this activity are increased understanding of the basic principles of human resource management, improved coordination among team members, and increased productivity and quality of service in the hospital. Through this training, it is hoped that hospitals can continuously improve their competitiveness and patient and family satisfaction